An analysis of gender inequality on black women characters in hidden figures film - Laula Hanna Maryam; Lina Tri Astuty; ami Pradana (Literary Criticism, 2022)
AbstractThis research discusses gender inequality on black women characters in "Hidden Figures" Film. The objectives of this research are to find gender inequality and to show what factors that cause gender inequality in “Hidden Figures” film. This research used the descriptive qualitative method. This is related to the description of the data in the form of a conversation in film. Analysis in this research using analysis from spreadlay and theory from Fakih and Relawati. The results of this reseacrh indicate that there are two types of gender inequality found namely marginalization and subordination. In addition there are four factors that cause gender inequality in “Hidden Figures”film , namely the factor of public confidence in the myth, factor of rationality, factor of Patriarchy and Factor of Capitalist System.Keyword: Film, Gender Inequality, Factor, Hidden Figures